Micromorphology and microstructure of coal fly ash and furnace bottom slag based light-weight geopolymer. (10th May 2020) - Zhou, Xinxing; Shen, Junmin
Graphical abstract: Highlights: Molecular and numeric models of light-weight geopolymer were built. This study explores the micromorphology and microstructure of light-weight geopolymer. The hydration mechanisms of light-weight geopolymer were investigated by a new method. Abstract: The annual output of coal fly ash and furnace bottom is ca.7.2 billion tons and ca.4.5 billion tons in China, respectively, which affected seriously human health and ecological safety. In order to enhance the mechanical strength and durability of geopolymer and take full use of solid waste, the coal fly ash and furnace bottom slag were added into the light-weight geopolymer. This study explores the micromorphology and microstructure of light-weight geopolymer under the different SiO2 /Al2 O3 ratio and the maintenance time. Molecular dynamic simulation (MD), numerical simulation, and scanning electronic microscope (SEM) were used to investigate the micromorphology and microstructure of light-weight geopolymer. Numerical simulation was used to study the hydration mechanisms of light-weight geopolymer. The compressive strength of light-weight geopolymer ranged from 15 MPa to 62 MPa with the increase of alkaline activators content. The mechanical proprieties such as Young modulus, bulk modulus, shear modulus of light-weight geopolymer increased 3–5 times when the SiO2 /Al2 O3 ratio is 3.0. Laboratory results reveal that the SiO2 /Al2 O3 ratio affects the polymerization by influencing the formation of zeolites microstructure. The maintenance time could affect the micromorphology and hydration reaction of light-weight geopolymer. Simulation results show that coal ash affects the early hydration reaction of light-weight geopolymer, while the furnace bottom slag affect the last hydration reaction. In the late of hydration reaction, the internal layer production expanded out and formed the network structure.